Motor dysfunction and behavioural problems frequently coexist with congenital heart disease in school‐age children. (11th April 2014) - Liamlahi, R; von Rhein, M; Bührer, S; Valsangiacomo Buechel, E R; Knirsch, W; Landolt, M A; Latal, B
Abstract Aim Patients with congenital heart disease are at risk of neurodevelopmental deficits. Impairments in motor and behavioural function occur frequently, but no information is available concerning the coexistence of deficits in these two developmental domains. This study explored the occurrence of motor and behavioural deficits and their coexistence in children with surgically corrected congenital heart disease. Methods Outcome was assessed in 95 children with congenital heart disease who had undergone cardiopulmonary bypass surgery. Their mean age was 9.6 years (SD 2.5). Motor function was assessed with the Zurich Neuromotor Assessment and behaviour with the Strength and Difficulties Questionnaire. Results Children with congenital heart disease performed poorer in all motor domains compared with the reference population (all p ≤ 0.001). Behaviour was affected in the domains 'emotional symptoms' and 'hyperactivity/inattention' (both p < 0.01), and 54% of the children with motor abnormalities showed behavioural deficits. Children with coexistent abnormalities in behaviour and motor function had higher rates of remedial school services and therapeutic support. Conclusion Children with congenital heart disease are at risk of long‐term motor and behavioural problems, and there is a high rate of coexistence of problems in both domains. Early and longitudinal assessment of all developmental domains is necessary to provide adequate early support.